The role of Korean drama promoting tourism among Malaysian / Teh Pek Yen - Teh, Pek Yen (2016)
South Korea tourism industry has blossomed and become one of the most competitive travel destinations among Asian countries. One of the critical factors that triggered the development of tourism was the emergence of the Hallyu phenomenon in the 1990s; Korea started to export drama series to neighbouring countries such as Japan, China, Vietnam, Thailand, Indonesia, Singapore, and Malaysia. Since then, tourists have been eager to visit filming locations and experience the culture of Korea. Out of the South East Asian countries, Malaysia ranked as the second highest provider of inbound tourists in South Korea, after Thailand. Hence, the Hallyu craze has proven to be the most attractive component to capture the interest of Malaysian tourists. As a result, Hallyu has provoked research interest by scholars. Many works have been done regarding Hallyu and Korean drama, and tourism is a major area of research. Empirical studies have focused on the impacts of Korean drama on countries like China, Taiwan, Japan and Singapore. Although Malaysia is one of the significant countries influenced by the Hallyu effect, very little research has been conducted; particularly on the impact of tourism. Consequently, Malaysia provides a unique context where the population is multi-racial and include bumiputera (Malay and indigenous), Chinese, Indian, and other minority groups as compared to other Hallyu-crazed countries that are generally monoethnic. Therefore, this study has conducted a research which involves three objectives: i) discover the relationships between tourist backgrounds and travelling process (motivation, experience, and satisfaction), ii) determine impacts of K-drama on the travelling process, and iii) discover the attributes of projected images from K-drama. The research framework was divided into four path models and 24 sub-hypotheses were tested with each model employed to examine a different research problem. Creswellï¿½s iv mixed method approach was employed in this study. Questionnaire surveys and interviews were conducted at the Incheon International Airport and hostels in Seoul from October to December 2012. The targeted respondents were Malaysian leisure tourists who had been in Korea for two or more days. In addition, interviews were conducted with relevant organizations in order to provide multiple approaches to measure the research problems. Data were analysed by employed inferential statistics (T-test, MANOVA, and Canonical Correlation Analysis) and content analysis (provisional coding, descriptive coding, and axial coding). The findings contribute two aspects to the research that include managerial and academic practices. From the managerial aspect, Korean drama can be used as a marketing tool to induce development of new destinations. This helps to reduce the overburdened capacity of the high density or heavily populated destinations. In addition, the study proposes that Korean drama should be perceived as a cultural platform which helps to transmit culture and customs of the host to potential tourists prior to a trip. The findings have shown that many Malaysian tourists belonged to the younger generation and more importantly, many of them were Malays who were usually very particular in choosing travel destinations that facilitated Muslim practices. From the academic aspect, this is a potential platform to reduce cultural conflicts between hosts and tourists as this issue has been a concern of academics and relevant stakeholders. Lastly, the findings have allowed the proposal of four new dimensions of images projected from K-drama. Although the results indicated that the images have significant impacts on the travelling process, observations of these impacts will be able to be refined and improved in future studies.